Analyzing and Understanding Network Politics - Wang, Baisong (IJRDO - Journal of Social Science and Humanities Research, 2019)
Cyber politics is a new branch of science that has been formed and has developed since the 1990s. The cyberspace has had a profound influence over the political system, political process, political power and international relations. With the development of information technology, cyber politics has emerged as the times demand. Cyber politics, which is an important theoretical branch of politics, has presented the urgent request about the development of traditional theory of politics. The thesis further analyzes its basic features, basic contents, influence and predicts its development tendency in the future based on the understanding of the definition of network politics.